Elementary Differential Geometry - Christian Bar (New Delhi Cambridge University Press, 2022)
School of Mathematics and Natural Science
MIR No.: 198
Order Date: 2024-07-29
Order No: CU/OPEX/LIBRARY/23/2024-25
Received Date: 2024-11-11
Keywords: Mathematics, Geomtery, Differential Geometry